Naming grace : preaching and the sacramental imagination - Hilkert, Mary Catherine (New York : Continuum, 1997)
"It is not a lack of training in the art of rhetoric that accounts for the ineffectiveness of preaching within the Christian churches. More significant is the lack of adequate theological foundations. While recognizing the great contribution that neo-orthodoxy and the "dialectical imagination" have made, Hilkert's major contribution is a scholarly examination of the resources of the "sacramental imagination."
The Good News in different voices.
Keywords: Catholic church -- Doctrines; Preaching; Catholic preaching; Grace (Theology); Sacraments -- Catholic Church; Imagination -- Religious aspects -- Catholic Church; Feminist theology